Nutritional Status of Toddlers in Klaten: A Case Report - Fitriana Noor Khayati; Fitri Suciana; Nur Wulan Agustina; Dinda Risky Tiara (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Background: Good nutritional status is very important for infant growth. A good nutritional status will support growth, development, energy production, body defense, brain structure and function. Nutritional problems suffered by babies can have serious consequences for their health and their future. Poor nutrition can cause the baby to be prone to disease and stunted body tissue growth. Objective: To understand the characteristics of the respondents and to know the description of the nutritional status of children under five in the village of Sidorejo, Kemalang, Klaten. Methods: Design This study is a quantitative descriptive study. This research was conducted to determine the description of the nutritional status of children under five in the village of Sidorejo, Kemalang. The sampling technique in this study was total sampling. The sample in this study was 31 toddlers. The instrument used in this study was a demographic data questionnaire that was filled out via google form. Results: The characteristics of toddlers who were respondents in this study were at least 0 months and a maximum age of 52 months with an average age of 17.45 months and more of the toddlers who were female with a percentage of 54.8%. The results of this study were the nutritional status of children under the category of good nutrition, which was 61.3% compared to children who had less nutrition with a percentage of 19.4%, malnutrition with a percentage of 12.9%, and over nutrition with a percentage of 6,5%.